2022
DOI: 10.1371/journal.pone.0270915
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac glycoside-mediated turnover of Na, K-ATPases as a rational approach to reducing cell surface levels of the cellular prion protein

Abstract: It is widely anticipated that a reduction of brain levels of the cellular prion protein (PrPC) can prolong survival in a group of neurodegenerative diseases known as prion diseases. To date, efforts to decrease steady-state PrPC levels by targeting this protein directly with small molecule drug-like compounds have largely been unsuccessful. Recently, we reported Na,K-ATPases to reside in immediate proximity to PrPC in the brain, unlocking an opportunity for an indirect PrPC targeting approach that capitalizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…To evaluate this characteristic experimentally in a relevant model, immortalized human cells (ReN VM cells) that we had differentiated to acquire neural or astrocytic characteristics were exposed for a duration of one week to low nanomolar levels of oleandrin or 15 KDC203. Following cell lysis, steady-state ATP1A1 levels were assessed by western blot analysis to determine if the ligand-receptor interactions had caused the previously observed reduction in ATP1A1 levels [18]. This analysis established that KDC203 had indeed similar potency as oleandrin on the basis that both drugs achieved a similar reduction in ATP1A1 levels when added at 4 nM concentration to the cell culture medium (Fig 6A).…”
Section: In Vitro Assessment Of Potency In Differentiated Ren Vm Cellsmentioning
confidence: 76%
See 3 more Smart Citations
“…To evaluate this characteristic experimentally in a relevant model, immortalized human cells (ReN VM cells) that we had differentiated to acquire neural or astrocytic characteristics were exposed for a duration of one week to low nanomolar levels of oleandrin or 15 KDC203. Following cell lysis, steady-state ATP1A1 levels were assessed by western blot analysis to determine if the ligand-receptor interactions had caused the previously observed reduction in ATP1A1 levels [18]. This analysis established that KDC203 had indeed similar potency as oleandrin on the basis that both drugs achieved a similar reduction in ATP1A1 levels when added at 4 nM concentration to the cell culture medium (Fig 6A).…”
Section: In Vitro Assessment Of Potency In Differentiated Ren Vm Cellsmentioning
confidence: 76%
“…This analysis established that KDC203 had indeed similar potency as oleandrin on the basis that both drugs achieved a similar reduction in ATP1A1 levels when added at 4 nM concentration to the cell culture medium ( Fig 6A ). However, whereas oleandrin was toxic at concentrations exceeding 4 nM [18], KDC203 was tolerated by the cells at all concentrations tested in this initial pilot experiment. Remarkably, exposure of ReN VM cells for one week to 8 or 16 nM levels of this compound led to additional reductions in ATP1A1 levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently discovered that PrP C is surrounded by Na,K-ATPases (NKAs) in the brain [ 17 ], which led us to propose an indirect targeting approach [ 18 ]. We showed that when cardiac glycosides (CGs), a class of compounds also known as cardiotonic steroids, bind to NKAs, it causes their internalization and degradation.…”
Section: Introductionmentioning
confidence: 99%